Some Performance Indicators of Financial Companies that have Implemented Digital Transformation Process in Honduras between 2018-2022 - Durón Esquivel, Gabriel Enrique; Torres Vindas, Javier Antonio (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To determine the impact on the performance of Honduran financial companies between 2018-2022 due to the organizational change resulting from digital transformation. MATERIAL AND METHOD: A quantitative, non-experimental, longitudinal, correlational-causal study was conducted and structural equation modeling (PLS-SEM) was used for the empirical analysis. Data were obtained from the financial statements and management reports of a bank in Honduras for the period 2018-2019. The model is based on the causal relationship of four hypotheses. RESULTS: It can be inferred that in financial entities the management of planned organizational change has a positive and significant impact on the total performance observed in a period of time; which is reinforced in a positive and significant way through the emerging managerial adjustments, which are taken based on the available evidence; adding the digital transformations that allow managing in an efficient and effective way such organizations. CONCLUSIONS: The predictive model of this research, shows us that the success in the performance of a financial entity is based on three causal indicators: the planning of organizational change, the implementation of digital transformations and the ability of managers to make organizational adjustments according to the observed performance.